2022
DOI: 10.3389/fgene.2022.786689
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related lncRNAs Signature Predicts Clinical Prognosis and Is Associated With Immune Landscape in Pancreatic Cancer

Abstract: Pancreatic cancer is one of the most lethal malignancies and currently therapies are severely lacking. In this study, we aimed to establish a novel ferroptosis-related lncRNAs signature to predict the prognosis of patients with pancreatic cancer and evaluate the predictive abilities of candidate lncRNAs. According to The Cancer Genome Atlas (TCGA) database, a total of 182 patients with pancreatic cancer were included in our study. Ferroptosis-related lncRNAs were screened by Pearson correlation analysis with 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Among the seven lncRNAs used to construct the signature, AC092171.5 has previously been reported as an immune-and m6A-related lncRNA in pancreatic cancer and is significantly associated with patient prognosis (Wei et al, 2019;Cao et al, 2022). CASC8 has been suggested as a marker to predict the prognosis of PAAD and as a potential target for treatment (Wang et al, 2020;Ping et al, 2022), which is consistent with our findings. AC090114.2 was reported to be a pyroptosis-related lncRNA and was associated with PAAD prognosis and tumor immune microenvironment Frontiers in Genetics frontiersin.org (Zhao et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Among the seven lncRNAs used to construct the signature, AC092171.5 has previously been reported as an immune-and m6A-related lncRNA in pancreatic cancer and is significantly associated with patient prognosis (Wei et al, 2019;Cao et al, 2022). CASC8 has been suggested as a marker to predict the prognosis of PAAD and as a potential target for treatment (Wang et al, 2020;Ping et al, 2022), which is consistent with our findings. AC090114.2 was reported to be a pyroptosis-related lncRNA and was associated with PAAD prognosis and tumor immune microenvironment Frontiers in Genetics frontiersin.org (Zhao et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, LINC01281 is considered a protective factor for laryngeal cancer [ 37 ]. Ping et al identified a ferroptosis-related lncRNA prognostic signature that included PAN3-AS1 and found it associated with a favorable prognosis in cancer patients [ 38 ]. HEIH is highly expressed in several tumor types; can promote tumor cell proliferation, migration, invasion, and drug resistance; and is related to a poor prognosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since rst named by Dixon in 2012, ferroptosis has been demonstrated in the regulation of metabolism and redox biology, affecting the pathogenesis and treatment of cancers. The prognostic signatures based on ferroptosis related lncRNAs have been investigated to play essential roles in predicting survival and outcomes of patients with various cancers, including hepatocellular carcinoma (19), renal cancer (11), pancreatic cancer (20), oral squamous cell carcinoma ( 21) and so on. Cuproptosis a novel form of copper-induced cell death has been reported to be regulated by 16 mRNAs as described above.…”
Section: Discussionmentioning
confidence: 99%